2015
DOI: 10.3329/baj.v17i2.24652
|View full text |Cite
|
Sign up to set email alerts
|

Four crops based cropping pattern studies for increasing cropping intensity and productivity in Rajshahi region of Bangladesh

Abstract: A field trial was conducted at the Regional Wheat Research Centre of Bangladesh Agricultural Research Institute (BARI), Rajshahi to study the comparative agronomic performance and economic return of four crops based cropping patterns. The cropping patterns were as follows: CP1= Transplanted Aman rice (cv. Binadhan-7)–Mustard (cv. BARI Sarisha14)–Boro rice (cv. BRRI dhan28) – Transplanted Aus rice (cv. Parija); CP2= T. Aman rice–Potato (cv. Diamont)–Boro rice–T.Aus rice; CP3=T. Aman rice–Mustard (cv. BARI Saris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 0 publications
2
17
0
Order By: Relevance
“…Yield and economic performance of alternate and existing cropping pattern during 2014-15 and 2015-16 are presented in Hossain et al (2014) who stated that short duration varieties and improved four crop based cropping pattern increases total productivity and profitability over farmers existing pattern.…”
Section: Yield and Productivity Of Cropping Patternmentioning
confidence: 99%
“…Yield and economic performance of alternate and existing cropping pattern during 2014-15 and 2015-16 are presented in Hossain et al (2014) who stated that short duration varieties and improved four crop based cropping pattern increases total productivity and profitability over farmers existing pattern.…”
Section: Yield and Productivity Of Cropping Patternmentioning
confidence: 99%
“…Mondal et al (2015) reported that T. Aman rice (var: Binadhan-7) -Mustard (var:BARI Sarisha-15) -Mungbean (var:BARI Mung-6) -T. Aus rice (var: Parija) cropping pattern gave higher benefit with reasonable cost of production and could be easily fitted in the existing pattern. Hossain et al (2014) also reported that T. Aman rice (var. Binadhan-7) -Mustard (var.BARI Sarisha-15) -Mungbean (var.BARI Mung-6) -T. Aus rice (var.…”
Section: Introductionmentioning
confidence: 93%
“…Mondal et al (2015) reported that T.Aman rice (var: Binadhan-7) -Mustard (var: BARI Sarisha-15) -Mungbean (var: BARI Mung-6) -T.Aus rice (var: Parija) cropping pattern gave higher benefit with less cost of production and could be easily fitted in the existing pattern. Hossain et al (2014) also reported that T.Aman rice (var: Binadhan-7) -Mustard (var: BARI Sarisha-15) -Mungbean (var: BARI Mung-6) -T.Aus rice (var: Parija) are agronomically feasible and economically profitable compared to the existing pattern.Due to growing four crops in a year in the same piece of land more employment opportunity could be created and at the same time due to increased production of crops, food and nutritional security could be ascertained for the farmers and at the same time cropping intensity and productivity could be increased (Mondal et al, 2015;Hossain et al, 2014). Nazrul et al (2017) found that improved pattern (Mungbean-T.Aus -T.Aman rice) provided higher grain yield, contributed more REY, gave maximum sustainable index, production efficiency, land use efficiency and higher profit compared to farmers pattern (Fallow-T.Aus-T.Aman rice).…”
Section: Introductionmentioning
confidence: 95%